Study on the Use of Synthetic Organic Fertilizer Formulations on the Growth and Yield of Upland Water Spinach (Ipomoea reptans) - Nabila, Ria; Indarwati, Indarwati; Sa'adah, Tatuk Tojibatus (Journal of Applied Plant Technology, 2025)
This study aimed to evaluate the effect of various types of synthetic organic fertilizers on the growth and yield of upland water spinach (Ipomoea reptans). The research was conducted in open field conditions using a Randomized Complete Block Design (RCBD) with three treatments: P1: control (urea); P2: Nutrizim granular organic fertilizer; P3: Nutrizim crumb organic fertilizer, each replicated three times. (a) The use of synthetic organic fertilizers had a significant effect on growth parameters, including number of leaves, plant height, and fresh weight of upland water spinach. (b) The plants treated with Nutrizim granular fertilizer produced a fresh weight yield of 36.15 tons/ha, which was not significantly different from the control treatment (47.61 tons/ha), with a yield difference of 11.46 tons between the Nutrizim granular fertilizer and the control. Thus, the use of Nutrizim granular organic fertilizer can support the growth and yield of upland water spinach.